PHYTOCHEMICAL SCREENING AND ANTIOXIDANT ACTIVITY ASSESSMENT OF YELLOW WOOD ROOT (ARCANGELISIA FLAVA (L.) MERR.) USING THE FRAP AND ABTS METHOD - Maria Sheryll Oktaverlyn; Noer Saelan Tadjudin; Eny Yulianti; Frans Ferdinal (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2026)
Background: Yellow wood root/ Arcangelisia flava, a traditional medicinal plant commonly used in Kalimantan, Indonesia, has been found to possess strong antioxidant properties. Although previous studies have reported that this plant contains certain phytochemicals and exhibits antioxidant activity, other specific phytochemical composition of the root and its antioxidant capacity using the FRAP and ABTS method remain poorly understood. Objective: This study aimed to examine the phytochemical content and antioxidant activity of the methanol extract from Arcangelisia flava (yellow wood) root. Methods: The research was conducted using an in vitro experimental approach to evaluate the presence of secondary metabolites and antioxidant capacity through the Ferric Reducing Antioxidant Power (FRAP) and 2,2′-azinobis-(3-ethylbenozothiazoline-6- sulfonate) (ABTS) assays. Extraction was performed on 75 grams of dried yellow wood root simplicia using methanol as the solvent, yielding 21.57 grams of extract (28.76%). Results: Phytochemical analysis detected a range of secondary metabolites including alkaloids, terpenoids, phenolics, quinones, saponins, tannins, coumarins, betacyanins, cardiac glycosides, flavonoids, and glycosides, while steroids and anthocyanins were not detected. The antioxidant activity was measured at extract concentrations of 10-30 μg/mL. In the FRAP assay, the extract reduced Fe³⁺ to Fe²⁺ with an IC₅₀ value of 17.48 μg/mL, while in the ABTS assay, it neutralized free radicals with an IC₅₀ of 21,99 μg/mL. Both results indicate a strong antioxidant potential and are comparable to the Trolox standards (IC₅₀ = 10.54 μg/mL and 13.27 μg/mL, respectively). Conclusion: These findings support the traditional use of Arcangelisia flava (L.) Merr., suggesting its potential as a source of natural antioxidants. Further research is recommended to explore its mechanisms and potential applications in health and disease prevention.